Discriminatory Ability of Visceral Adiposity Index (VAI) in Diagnosis of Metabolic Syndrome: A Population Based Study - Motamed, N.; Khonsari, M. R.; Rabiee, B.; Ajdarkosh, H.; Hemasi, G. R.; Sohrabi, M. R.; Maadi, M.; Zamani, F. (Experimental and Clinical Endocrinology & Diabetes, 2017)
Background Visceral adiposity index (VAI) has been suggested as an index of visceral adiposity. This study was conducted to determine the discriminatory ability of VAI in diagnosis of metabolic syndrome (MetS).Methods and materials We used the data of 5 312 subjects aged 18–74 years of a cohort study conducted among 6 140 individuals aged 10–90 years in Amol, northern Iran. The city population was divided into 16 strata based on gender and age groups in 10-year intervals. The subjects were randomly selected from each stratum. MetS was defined based on National Cholesterol Education Program Adult Treatment Panel III (NCEP/ATPIII), American Heart Association/National Heart, Lung and Blood Institute (AHA/NHLBI) update of Adult Treatment Panel III (ATPIII), International Diabetes Federation (IDF) and joint interim statement (JIS) definitions. The discriminatory ability of VAI and other obesity measures were evaluated using receiver operating characteristic (ROC) curves.Results While waist circumference (WC) showed the highest discriminatory ability for MetS in IDF definition in men (AUC=0.899 [CI=0.888–0.910]), VAI had the greatest discriminatory ability according to other definitions in men and women. The related AUCs of VAI were 0.866 (95%CI: 0.850–0.881), 0.829 (95%CI: 0.813–0.846), 0.859 (95%CI: 0.844–0.873) and 0.876 (95%CI: 0.863–0.889) based on NCEP/ATPIII, AHA/NHLBI update of ATPIII, IDF and JIS definition in men, and also 0.888 (95%CI: 0.875–0.902), 0.894 (95%CI: 0.881–0.907), 0.883 (95%CI: 0.869–0.897) and 0.879 (95%CI: 0.864–0.894) in women, respectively.Conclusion VAI showed an excellent discriminatory ability in diagnosis of MetS. Considering its relatively simple calculation, this index could be suggested as a reliable tool in medical practice.
Keywords: visceral adiposity index; metabolic syndrome; discriminatory ability; adiposity